Decreased efficiency of pollen collection due to Sulfoxaflor exposure leads to a reduction in the size of bumble bee workers in late European summer - Boff, Samuel; Keller, Alexander; Raizer, Josué; Lupi, Daniela (Frontiers in Ecology and Evolution, 2022)
Bumble bees (Bombus terrestris) are important pollinators of wild and crop plants. Despite their importance in the process of fruit and seed production on crop sites, their activity may be impaired due to exposure to pesticides. This species has a yearly life cycle and colony success may rely on effective foraging of workers on ruderal plants late in summer when most crops are no longer flowering. In the current study we investigated the effect of a chronic exposure to Sulfoxaflor on aspects of foraging behaviour and whether Sulfoxaflor influences body size of workers of B. terrestris in a crop landscape. We found that two weeks of continuous exposure to Sulfoxaflor influenced workers’ foraging dynamics and collection of resources. However, there was no evidence that the 5 ppb dose of the pesticide impacted the ability of bees to handle flowers with different traits. Workers from colonies exposed to Sulfoxaflor were smaller. The effect on worker size may be explained as a consequence of the reduced pollen income per unit of worker foraging. Thus, if the effects of Sulfoxaflor applied directly to crops has the same effect as that observed on commercial bumble bees after our chronic exposure, it might negatively impact colony success due to the impact on pollen collection and the reduction in the size of workers.